An Analysis of Cognitive Domain Level on Speaking Activities in 2013 Curriculum English Textbook for Grade XI - Deswita Rahmadani; Adnan Aryuliva (Universitas Negeri Padang, 2021)
This research was conducted to find out whether the speaking skill activities in 2013 Curriculum English textbook can provoke the thinking skills of the students to be HOTS or LOTS. This research was also conducted to find out the dominant cognitive domain level in this English textbook. The content analysis research was used in this research. The source data in this research was speaking activities in 2013 Curriculum English textbook entitled “Pathway To English “for grade XI. This English textbook was published by Erlangga Publisher. A table analysis was used to analyze the data in this research. This table analysis was adapted from Igbaria (2014). The result of this research showed that speaking activities in this English textbook were categorized as high order thinking skills criteria. From 46 speaking activities found in this textbook, the final total of speaking activities that included high order thinking skills were 26 speaking activities (56.52%). The result of the cognitive domains thinking skills process reflected a slight difference because the total speaking activities included low order thinking skills were 20 speaking activities (43.48%). The dominant cognitive domain level found on these speaking activities was the creating level (25 speaking activities).